2020
DOI: 10.3390/w13010077
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic Toxicity of Photocatalyst Nanoparticles to Green Microalgae Chlorella vulgaris

Abstract: In the last years, nanoparticles such as TiO2, ZnO, NiO, CuO and Fe2O3 were mainly used in wastewater applications. In addition to the positive aspects concerning using nanoparticles in the advanced oxidation process of wastewater containing pollutants, the impact of these nanoparticles on the environment must also be investigated. The toxicity of nanoparticles is generally investigated by the nanomaterials’ effect on green algae, especially on Chlorella vulgaris. In this review, several aspects are reviewed: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 85 publications
0
5
0
1
Order By: Relevance
“…The biotoxicity of nickel oxide NPs on Chlorella vulgaris was caused by their unavoidable effects on the development of aquatic photoautotrophs, cellular toxicity, morphological alteration, cell deterioration, and oxidative stress. These effects were related to the concentration of NPs and the production of ROS [53]. Silver NPs (Ag-NPs) are widely used in a variety of applications and have antimicrobial properties.…”
Section: Effect Of Nps On Microalgal Toxicitymentioning
confidence: 99%
“…The biotoxicity of nickel oxide NPs on Chlorella vulgaris was caused by their unavoidable effects on the development of aquatic photoautotrophs, cellular toxicity, morphological alteration, cell deterioration, and oxidative stress. These effects were related to the concentration of NPs and the production of ROS [53]. Silver NPs (Ag-NPs) are widely used in a variety of applications and have antimicrobial properties.…”
Section: Effect Of Nps On Microalgal Toxicitymentioning
confidence: 99%
“…A pesar del amplio uso del NPTiO2, su implementación para el tratamiento de aguas es un tema polémico, ya que muchos investigadores reportan que el NPTiO2 pudiera ser tóxico en los ecosistemas y en los seres humanos, dado que pueden originar inhibición en el crecimiento de la microalgas p.e. Chlorella vulgaris (Xia et al, 2018;Adochite et al, 2021), y en algunos microinvertebrados puede inducir una condición de estrés oxidativo en presencia de luz UV-A, lo cual conlleva a daños celulares, genotoxicidad, inflamación, alteraciones en las respuestas inmunológicas, entre otros perjucios moleculares y fisiológicos (Skocaj et al, 2011;Pérez-Arizti et al, 2020;Santana et al, 2021). Sin embargo, nuestro estudio demuestra la inocuidad del NPTiO2 para la microalga T. chuii y el rotífero B. plicatilis, garantizando así su crecimiento.…”
Section: Cultivo De Tetraselmis Chuii Y Brachionus Plicatilisunclassified
“…Furthermore, as a novel approach the release of these "emerging nanoparticles" such as PANI-ZnO composites also deserve to be investigated with respect to their possible ecotoxicological impacts on the environment [63,64]. Comparison of PZI and PZS specimens demonstrated that both preparation methods could be considered as successful in case that MB as a cationic dye was used as the model compound and the light source was specially chosen to exclude any direct photolysis of the substrate.…”
Section: Effect Of Initial Dye Concentrationmentioning
confidence: 99%